Tide-storm-dominated shelf sequence of the Neoproterozoic Blaini Formation and its implications on the sedimentation history of Krol-Belt, Kumaun Lesser Himalaya, India - Pant, Charu C.; Goswami, Pradeep K. (Journal of Nepal Geological Society, 2003)
The diamictite bearing Neoproterozoic Blaini Formation constitutes a significant lithostratigraphic unit of the Lesser Himalayan sedimentary pile. These diamictite bearing horizons have implication for the genetic evolution of the Krol-belt. Detailed lithofacies and palaeocurrent analyses of the Blaini Formation suggest that the sediments belong to two distinct facies associations. These are: Strom Dominated Facies Association and Tide Dominated Facies Association. The Strom dominated Facies Association overlies a transgressive lag deposit and comprises offshore, offshore transition and subtidal facies. The ride Dominated Facies Association on the other hand comprises intertidal to supratidal facies. The Blaini succession in the Nainital area overlies the Nagthat siliciclastics deposited in a barrier island set-up having a sharp to erosional contact. The Nagthat Sea gave way to shelf sedimentation of the Blaini times. The high-energy-tide-storm condition of sedimentation in the basin had witnessed mode rate to low energy conditions intermittently, wherein diamictites were emplaced through down slope re-sedimentation of cohesive debris flow. The debris was originated by intermixing of extra-basinal and intra-basinal clasts along with hinterland sediments, which were transported in response to some tectonic adjustments during the terminal stages of Blaini sedimentation. Subsequent tectonic stability and quiescence gave way to thick stromatolitic carbonate succession during the Krol times. The Krol-belt as such is evolved in three distinct cycles of sedimentation, distinguished as the Jaunsar-Simla, the Blaini and the Krol cycles.